The Causes of Mental Health Problems Among Construction Professionals in Malaysia - Subramaniam, Umah Devi; ABU BAKAR, HASNIZA (Recent Trends in Civil Engineering and Built Environment, 2021)
Construction activities in Malaysia were in a stressful environment for the workers and it consist of various and higher demands. Employers are becoming more sophisticated in the modern Malaysian construction industry causing greatly increased the benchmarking for the efficient delivery of construction projects which have contributed construction professionals’ mental health problems . This problems can only be solved when there are proper identification of the factors causing the problems. Thus, this research comprises two main objectives which are to identify the significant factors causing mental health problems among construction professionals and to analyze the major factors influencing the impacts of mental health problems. Thus, the research method of this study has used an analysis of literature review and questionnaire survey. The assessment will involves construction professionals such as architects, engineers, project managers and supervisors. There were 110 questionnaires received from the construction professionals from all over Malaysia. Therefore, for assessing the factors that cause mental health problems among construction professionals that have been identified from the literature review and the average index method has been used for the analysis. The job characteristics and demand factors: high-pressure workplace, poor working environment, long working hours; organisation factors: organisational policies, treatment and reward; health problem factors: high risk of accidents and unwell condition have been highlighted to be the extremely significant factors that should be taken into concern. The major factors and their influence towards the impacts of mental health problems were analyzed using average index (AI) method. The ways to control mental health problems was analyzed using mean score (MS) method and ranking method. The result showed that controlling work-related demands, taking part in relaxation trainings, adapting positive attitudes, conducting regular exercise and reducing harmful exposure in workplace can be a useful guide for practitioners in controlling mental health problems among construction professionals and also reduce the impacts caused by mental health problems.